Air Quality at Urban Transportation Nodes: A Case Study of SO₂, NO₂, and CO Concentrations in Palembang City - Yuwati, Sri; Gulo, Fakhili; Zulkarnain, Mohammad; Suheryanto, (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to analyze variations in sulfur oxide (SO₂), nitrogen oxide (NO₂), and carbon monoxide (CO) concentrations at eight major intersections in Palembang City.This study analyzed ambient air quality at eight major traffic nodes in Palembang City using SO₂, NO₂, and CO parameters. Measurements were carried out at a height of 2–3 meters according to US-EPA and WHO standards. SO₂ was determined using the West–Gaeke method, NO₂ with the Griess–Saltzman and chemiluminescence analyzer, while CO was measured using the Non-Dispersive Infrared (NDIR) method. All procedures were accompanied by recording of meteorological factors and instrument quality control. The results showed a significant difference between morning and afternoon, with higher average concentrations in the afternoon (SO₂: p = 0.014; NO₂: p = 0.000; CO: p = 0.003), which was influenced by traffic density and meteorological conditions. Pollutant concentrations tended to increase during rush hour at intersections with high vehicle flow. In contrast, inter-location analysis showed variations in pollutant concentrations, but they were not statistically significant (p > 0.05), indicating a relatively homogeneous distribution of traffic emissions in urban areas. Exposure to SO₂, NO₂, and CO has the potential to cause serious health impacts, including respiratory and cardiovascular disorders, as well as liver dysfunction due to oxidative stress and hypoxia. These findings emphasize the need for continuous air quality monitoring and transportation emission control policies in Palembang.